Pengaruh Promosi Shopee terhadap Perilaku Konsumtif pada Mahasiswa Manajemen Bisnis Syariah Stain Mandailing Natal - Ira Rizkia Ningsih; Andy Hakim; Vebri Sugiharto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out how much influence Shopee promotions have on consumer behavior among STAIN Mandailing Natal Sharia Business Management students. The sample used came from 75 MBS students using a purposive sampling method. The approach used is quantitative and in collecting primary data observation and questionnaire methods are used. Meanwhile, the data analysis that researchers used in this research was analysis using validity and reliability tests, classical assumption tests, simple linear regression tests and hypothesis tests, namely the t test and R Square test (with the help of the SPSS Version 24 program). The results of the research show that there is an influence of shopee promotional variables on consumer behavior among Mandailing Natal Sharia Business Management Students. Shown by the significance value of t 0.000 which is smaller than sig = 0.05 (0.000>0.05) the value of R = 0.629 and R Square = 3.96 means that Shopee promotion is able to explain the dependent variable or consumer behavior of 0.396 x 100 = 39.6 message while the other 60.4 percent is explained by other variables. Based on the research results, it can be concluded that Shopee promotions have a positive and significant effect on consumer behavior with a value of tcount < ttable or tcount > ttable (6.916 < 1.666 or 6.916 > 1.666). There is a positive and significant relationship between Shopee promotions and consumer behavior among students.